Sleep in adolescents of different socioeconomic status: A systematic review - Leite C.R.* (2015)
© 2015 Sociedade de Pediatria de São Paulo.Objective To analyze the sleep characteristics in adolescents from different socioeconomic levels. Data source Original studies found in the MEDLINE/PubMed and SciELO databases without language and period restrictions that analyzed associations between sleep variables and socioeconomic indicators. The initial search resulted in 99 articles. After reading the titles and abstracts and following inclusion and exclusion criteria, 12 articles with outcomes that included associations between sleep variables (disorders, duration, quality) and socioeconomic status (ethnicity, family income, and social status) were analyzed. Data synthesis The studies associating sleep with socioeconomic variables are recent, published mainly after the year 2000. Half of the selected studies were performed with young Americans, and only one with Brazilian adolescents. Regarding ethnic differences, the studies do not have uniform conclusions. The main associations found were between sleep variables and family income or parental educational level, showing a trend among poor, low social status adolescents to manifest low duration, poor quality of sleeping patterns. Conclusions The study found an association between socioeconomic indicators and quality of sleep in adolescents. Low socioeconomic status reflects a worse subjective perception of sleep quality, shorter duration, and greater daytime sleepiness. Considering the influence of sleep on physical and cognitive development and on the learning capacity of young individuals, the literature on the subject is scarce. There is a need for further research on sleep in different realities of the Brazilian population.